2004
DOI: 10.1086/380790
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Lipoatrophy Associated with Highly Active Antiretroviral Therapy in Human Immunodeficiency Virus–Infected Patients Switched from Stavudine to Abacavir or Zidovudine: The Results of the TARHEEL Study

Abstract: Stavudine use is a contributing factor for lipoatrophy, whereas use of abacavir or zidovudine is less likely to cause this complication. The TARHEEL study was a 48-week, open-label study that assessed changes in lipoatrophy after abacavir (86 patients [73%]) or zidovudine (32 patients [27%]), 300 mg twice daily, was substituted for stavudine for 118 human immunodeficiency virus (HIV)-infected patients (HIV type 1 RNA level, <400 copies/mL) with virological suppression who had developed lipoatrophy after > or =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(109 citation statements)
references
References 15 publications
9
96
1
3
Order By: Relevance
“…The positive clinical evolution after substituting TDF or ABV for stavudine was consistent with three studies from high-income countries (including two randomised controlled trials), demonstrating a slow and partial reversal of fat loss. 15,21,22 Only one uncontrolled study addressed the efficacy of substituting stavudine with ZDV or ABV. 15 In that study, some fat recovery was observed with ZDV although less pronounced than with ABV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive clinical evolution after substituting TDF or ABV for stavudine was consistent with three studies from high-income countries (including two randomised controlled trials), demonstrating a slow and partial reversal of fat loss. 15,21,22 Only one uncontrolled study addressed the efficacy of substituting stavudine with ZDV or ABV. 15 In that study, some fat recovery was observed with ZDV although less pronounced than with ABV.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that this support programme has had access to TDF and ABV we have been in the unique position of being able to follow patients who were switched to either ZDV or TDF/ABV. There has been only one study in the literature that used both ZDV and ABV for stavudine replacement, 15 but it did not directly compare the efficacy of the drugs and we would like to report on our experience. We previously reported a high level of lipoatrophy amongst patients on stavudine-containing first-line regimens within our antiretroviral treatment (ART) programme in Rwanda, using a standardized questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Lipoatrophy can be addressed by switching patients to another NRTI. Switching patients from stavudine to abacavir (preferred) or zidovudine improved fat distribution in HIV-infected patients [46].…”
Section: Lipoatrophymentioning
confidence: 99%
“…NRTI switching studies have shown that substituting abacavir for stavudine or zidovudine in patients with clinically apparent lipoatrophy [11,12] is associated with statistically significant improvements in fat wasting. However, absolute increases in limb fat are in the order of 1-2% and are often not apparent to either clinicians or patients, so it would seem prudent to focus on prevention of lipoatrophy, as fat restoration appears to be a slow and possibly incomplete process.…”
Section: Switching Strategies For Lipoatrophymentioning
confidence: 99%